Interests and Conflicts of Interest: Turkey’s Experiences from the Libyan Civil War - Ács, Sándor Bence (Journal of Central and Eastern European African Studies, 2025)
The overthrow of Muammar Gaddafi in 2011, followed by the outbreak of civil war in 2014, plunged Libya into complete chaos. The Government of National Accord (GNA), recognized by the majority of the international community, lost control over two-thirds of the country, where authority was assumed by the House of Representatives and the Libyan National Army (LNA) led by General Khalifa Haftar. As in so many other conflicts in the Islamic world, foreign actors with vested interests in the region quickly emerged in Libya as well—including Turkey, one of NATO’s most prominent military powers. During the conflict, Ankara swiftly found itself at odds not only with the supporters of the LNA, but also with states that, by virtue of their NATO membership, are technically its allies. The purpose of this paper is to explore the reasons behind Turkey’s military and political intervention in Libya, how these actions shaped Ankara’s relations with other actors involved in the conflict, and what strategic lessons Turkey gained from its involvement in the civil war.